Venous Structural Angulations and their Relationship with Insufficiency - Tosun, Alptekin; Hancerliogullari, Kadir Oymen; Serifoglu, Ismail; Keskin, Ozlem; Ozkaya, Enis (International Journal of Orthopedics and Rehabilitation, 2015)
Objective: The venous insufficiency of lower limb is a common complaint in the population. The natural history of CVD is not clear enough to satisfy. We have investigated the venous anatomy and reflux existence of the lower limb by using the structural angulations of the venous outlets and related this to the occurrence of venous reflux in the superficial, deep and perforator venous system, demonstrated on CDS. Methods: We investigate 44 limbs of 22 healthy subjects and 46 limbs of 23 patients with chronic venous disease (CVD). The participants were evaluated with duplex scanning for venous reflux. The CDS examination performed in the upright and supine position. Compression on gray-scale and color Doppler were employed to assess the absence of venous thrombosis. Result: 45 patients (31 female, 14 male) were examinated on doppler ultrasonography. The mean age was 54.5 years (41 to 79 years). All subjects were in normal range of body-mass-index and had no significant disease. We measured the vascular angulations on gray-scale ultrasonography. The measured the angulations of common femoral vein-saphenofemoral junction, saphenofemoral junction-vena saphena magna, common femoral vein-superficial femoral vein, common femoral vein-deep femoral vein and bifurcation of superficial femoral vein-deep femoral vein, respectively. Anatomical structural angulations were measured at 5 levels on sonography. Conclusion: The CDS is a definitive, economical and noninvasive safe diagnostic method in the diagnosis of CVD. This method appears to suggest a new imaginative approach with the measure of the angulations between venous vessel connections, consequently may predictive further CVD in early periods.